Pengaruh Kualitas Pelayanan, Promosi Dan Kepercayaan Terhadap Minat Beli Pengguna Shopee (Survey pada Pengguna E-Commerce Shopee di Klego Boyolali) - Bulan Setyaning Nugraheni; Retno Susanti; Sumaryanto (CV. ITTC INDONESIA, 2024)
The purpose of this research is to analyze the influence of service quality, promotion, and trust on the buying interest of Shopee users in Klego Boyolali. The research sample consists of 100 people who shop online on Shopee. The research uses purposive sampling technique. The research instrument test was conducted with validity and reliability tests, resulting in all questionnaire items for all variables being valid and reliable. The classical assumption test is conducted before performing inductive analysis, with results passing for all classical assumption tests, including multicollinearity test, autocorrelation test, heteroscedasticity test, and normality test. The research analysis methods include descriptive analysis, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The results of the descriptive analysis show that respondents rated the variables of service quality, promotion, and trust as very good, and rated buying interest as high. The results of the multiple linear regression analysis yielded regression equations Y = 1.506 + 0.118 X1 + 0.434 X2 + 0.805 X3 + e, indicating that service quality, promotions, and trust have a positive effect on buying interest. The t-test results indicate that service quality does not have a significant effect on purchase intention with a p-value of 0.290 > 0.05, while promotion has a p-value of 0.006 < 0.05 and trust has a p-value of 0.000 < 0.05, both significantly affecting buying interest. The F-test results show that this regression model has a calculated F value of 61.530 with a significance value (p-value) of 0.000 < 0.05, thus Ho is rejected and Ha is accepted, meaning the regression equation model is accurate. The result of the coefficient of determination (adjusted R²) shows that the coefficient of determination for this model is 0.647, meaning that the contribution of the independent variables X1 (Service Quality), X2 (Promotion), and X3 (Trust) to Y (Buying Interest) is 64.7%. The remaining 35.3% (100% - 64.7%) is explained by other variables outside the model, such as price, brand image, and risk service